Analysis of Plant Growth and Pest Incidence of Pakchoy Plants (Brassica rapa L.) Using the Wick System Hydroponics Through the Utilization of Catfish Waste - Yuliana, Anggi Indah; Hamidah, Syukriyana Fikri; Hartanti, Dyah Ayu Sri (AGARICUS: Advances Agriculture Science & Farming, 2024)
This study aimed to determine the effect of catfish wastewater as a source of nutrients in the hydroponic wick system cultivation model on the growth of pak choy mustard plants, which include: plant height, number of leaves, leaf area, pest and disease attacks, and plant yields. The method used in this study is a quantitative method with a Non-Factorial Randomized Block Design. This method used 6 treatments, namely (P0) 800 ml of water, (P1) 800 ml of water + AB Mix nutrients (A 5 ml + B 5 ml), (P2) 600 ml of water + 200 ml of catfish wastewater, (P3) 400 ml of water + 400 ml of catfish wastewater, (P4) 200 ml of water + 600 ml of catfish wastewater, (P5) 800 ml of catfish wastewater and repeated 3 times. The results showed that the treatment of 800 ml of catfish wastewater (P5) increased plant height, number of leaves, leaf area and weight of pakcoy plants in hydroponic wick system compared to the treatment of 800 ml of water (P0). Meanwhile, the attack of whitefly pests on pakchoy plants was found to be higher in all treatments of catfish wastewater as a source of nutrients in hydroponic wick system compared to the treatment of 800 ml of water + AB Mix nutrients (P1).